AN EMPIRICAL STUDY OF THE EFFECTS OF CUSTOMER SATISFACTION AND LOYALTY IN THE TELECOMMUNICATION INDUSTRY IN BANGLADESH (American International Journal of Nursing Education and Practice, 2022)
The primary objective of this study is to examine the impact of customer satisfaction within the specific setting of Bangladesh. The present study examined six key aspects: interactions, price structure, added value service, convenience, sales promotions, and customer service. The study utilized a combination of primary and secondary data sources to evaluate the predetermined hypotheses. The findings indicate that five characteristics, including communication, cost structure, value-added services, convenience, and customer service/care, have positive associations with consumer loyalty. Finally, the concept of telecommunication services in Bangladesh has recently been combined with ecological management in business. Therefore, this notion has lately taken into the customer satisfaction and survey with good and sound loyalty on this services. This study is based on customer responses to monitor their satisfaction against the major mobile operators in the country: Grameen Phone, Banglalink, Robi, and Teletalk. In order to determine satisfaction, we will ask questions to respondents about different criteria (such as network, Internet service, call rate price and value-added services, reliability, customer support etc.). This research aims to determine customer satisfaction with a wide range of services supplied by operators, as well as the correlation between service satisfaction (communication, price, value-added service, convenience, sales promotion, and customer service) and customer loyalty.JEL Classification Codes: Q56.